Nuclear doctrines and strategies : national policies and international security - Fitzpatrick, Mark (Senior fellow for non-proliferation); Nikitin, A. I. (Aleksandr Ivanovich), 1958-; Oznobishchev, Sergeĭ (NATO science for peace and security series. Human and societal dynamics ;, 2008)
Focuses on the overarching importance that nuclear strategies and doctrines continue to play in the modern world and in relations among the leading states.